Pengembangan Dan Validasi Metode Analisis Amlodipin Besilat Dan Cemarannya Dalam Sediaan Tablet - Muhammad Haqqi Hidayatullah; Slamet Ibrahim; Benny Permana (Pharmacon: Jurnal Farmasi Indonesia, 2022)
Amlodipine besylate belongs to the class of oral dihydropyridine calcium channel blockers that can be used to hypertension and angina therapy. Amlodipine as a pharmaceutical preparation must meet the criteria for a good pharmaceutical preparation, namely safe, efficacious and quality. In terms of safety, the presence of organic impurity in pharmaceutical products can affect the safety of medicinal products. Because the difficultness to obtain a standard of impurity, it is necessary to develop an analytical method to analyze the presence of contamination by stress testing. The analytical method was developed using a High Performance Liquid Chromatography (HPLC) instrument with Eclipse Plus C18 column 5 m (150 x 4.6 mm), mobile phase triethylamine (TEA): methanol in a ratio of 40:60 with isocratic elution and a flow rate of 1 mL/minutes and a wavelength of 237 nm with an injection volume of 10 µL. The results of the method validation showed good linearity with R2 of 0.9996, detection limit of 18.46 µg/mL and quantization limit value of 61.54 µg/mL. The value of the coefficient of variation on the precision parameter is 1.18-1.26%. The percent recovery accuracy value is 93.07-105.44% and the range value for proportional samples is in the concentration range of 24-84 µg/ml with R2 = 0.9993. The HPLC system meets all requirements for acceptance of the system conformity test. The results of this experiment showed that there were 2 out of 5 peaks of degradation products whose chemical structure was known. The application of the analytical method on commercial samples showed levels between 90.79-95.68% and there was no impurity in the product samples.